PERSEPSI SISWA TENTANG KOMPETENSI PROFESIONAL DAN MOTIVASI KERJA GURU TERHADAP HASIL BELAJAR SISWA - M Qahfi; Novianti Rahmawati; Tyty Nurhayati (STKIP MUHAMMADIYAH SAMPIT, 2020)
This study aims to determine Students' perceptions of professional competence and Teacher's Work Motivation on Student Learning Outcomes of Class VIII in Madrasah Tsanawiyah Negeri 1 Kotawaringin Timur Academic Year 2019/2020. The population in this study was eighth grade students of Madrasah Tsanawiyah Negeri 1 Kotawaringin Timur Academic Year 2019/2020, totaling 256 students. The technique used in collecting samples was proportional random sampling technique, so the number of samples was 80 students. Data collection techniques used were questionnaires and documentation. The results showed that there was no influence there was no effect of students' perceptions about professional competence and Teacher Work Motivation together on student learning outcomes indicated by the value of Fcount < Ftable is 0.465 < 3.11.